A = [ 1 3 2 4 ] B = 2 A
Enter your answer as the determinant of the matrix B .
Bonus: Generalise this result for any real number raised to the power any square matrix and provide a rigorous proof.
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
Let us take B = e ln 2 ⋅ A = e X = exp [ ( ln 2 3 ln 2 2 ln 2 4 ln 2 ) ] . Knowing that e x = Σ n = 0 ∞ n ! x n and that X = S Λ S − 1 , X n = S Λ n S − 1 (where Λ and S are respectively the eigenvalue and eigenvector matrices of X ), we can express B as the following:
B = I + 1 ! 1 X + 2 ! 1 X 2 + 3 ! 1 X 3 + . . . = S [ I + 1 ! 1 Λ + 2 ! 1 Λ 2 + 3 ! 1 Λ 3 + . . . ] S − 1 (i).
The eigenvalues of X can be computed according to:
det ( X − λ I ) = 0 ⇒ ∣ ∣ ∣ ∣ ln 2 − λ 3 ln 2 2 ln 2 4 ln 2 − λ ∣ ∣ ∣ ∣ = 0 ⇒ λ 2 − 5 ln 2 ⋅ λ − 2 ln 2 2 = 0 ⇒ λ = ( 2 5 ± 3 3 ) ⋅ ln 2 (ii).
If we substitute the eigenvalues of (ii) into (i), we now obtain:
B = S ⋅ ( Σ n = 0 ∞ n ! λ 1 n 0 0 Σ n = 0 ∞ n ! λ 2 n ) ⋅ S − 1 = S ⋅ ( exp ( ln 2 ⋅ 2 5 + 3 3 ) 0 0 exp ( ln 2 ⋅ 2 5 − 3 3 ) ) ⋅ S − 1 = S ⋅ ( 2 2 5 + 3 3 0 0 2 2 5 − 3 3 ) ⋅ S − 1 (iii).
Finally, det ( B ) = det ( S ) ⋅ det ( S − 1 ) ⋅ ∣ ∣ ∣ ∣ ∣ 2 2 5 + 3 3 0 0 2 2 5 − 3 3 ∣ ∣ ∣ ∣ ∣ = det ( S S − 1 ) ⋅ ∣ ∣ ∣ ∣ ∣ 2 2 5 + 3 3 0 0 2 2 5 − 3 3 ∣ ∣ ∣ ∣ ∣ = det ( I ) ⋅ ∣ ∣ ∣ ∣ ∣ 2 2 5 + 3 3 0 0 2 2 5 − 3 3 ∣ ∣ ∣ ∣ ∣ = 1 ⋅ 2 5 = 3 2 .
I'll provide a Laplace solution in alternative to brilliant @Mark Hennings solution.
It's a well-known fact that, for a real number r :
e r t = L − 1 { ( s − r ) − 1 }
Where L − 1 is the Inverse Laplace Transform . This reasoning extends to the matrix case as:
e A t = L − 1 { ( s I − A ) − 1 }
So for a matix A such as:
A = [ a c b d ]
We have:
e A t = L − 1 ⎩ ⎨ ⎧ [ s − a − c − b s − d ] − 1 ⎭ ⎬ ⎫
e A t = L − 1 { p ( s ) 1 [ s − d c b s − a ] }
Where p ( s ) = s 2 − ( a + d ) s + ( a d − b c ) is the characteristic polynomial of matrix A . Let us sat that the roots of p ( s ) are k and l . So, expanding in partial fractions:
e A t = L − 1 { k − l 1 [ s − k k − d + s − l d − l s − k c − s − l c s − k b − s − l b s − k k − a + s − l a − l ] }
e A t = k − l 1 [ ( k − d ) e k t + ( d − l ) e l t c e k t − c e l t b e k t − b e l t ( k − a ) e k t + ( a − l ) e l t ]
Making t = ln ( n ) , where n is a real number:
n A = k − l 1 [ ( k − d ) n k + ( d − l ) n l c n k − c n l b n k − b n l ( k − a ) n k + ( a − l ) n l ]
det ( n A ) = ( k − l ) 2 1 { [ ( k 2 − ( a + d ) + a d ) n 2 k + ( l 2 − ( a + d ) + a d ) n 2 l + + ( d k − d a − l k + a l ) n k + l + ( a k − l k − a d + d l ) n k + l ] − b c [ n 2 k + n 2 l − 2 n k + l ] }
det ( n A ) = ( k − l ) 2 1 [ n 2 k ( k 2 − ( a + d ) k + ( a d − b c ) ) + n 2 l ( l 2 − ( a + d ) l + ( a d − b c ) ) + + n k + l ( d k + d l + a k + a l − 2 a d + 2 b c − 2 l k ) ]
det ( n A ) = ( k − l ) 2 1 [ n 2 k p ( k ) + n 2 l p ( l ) + n k + l ( ( a + d ) ( k + l ) − 2 ( a d − b c ) − 2 k l ) ]
Notice that since k and l are roots of p ( s ) , p ( k ) = p ( l ) = 0 . Also notice that, by Vieta, k + l = a + d (sum of roots) and k l = a d − b c (product of roots). So:
det ( n A ) = ( k − l ) 2 n a + d [ ( k + l ) ( k + l ) − 2 ( k l ) − 2 k l ) ]
det ( n A ) = ( k − l ) 2 n a + d ( k − l ) 2
det ( n A ) = n a + d = n tr ( A )
In this case, n = 2 and tr ( A ) = 5 . So:
det ( 2 A ) = 3 2
Problem Loading...
Note Loading...
Set Loading...
We can find a nonsingular matrix P such that P A P − 1 is equal to the Jordan Normal form of A , and hence is of the form P A P − 1 = ( x 0 y z ) Thus P A n P − 1 = ( x n 0 y ( n ) z n ) n ≥ 0 for some y ( n ) ∈ R for all n ≥ 0 . Thus we can find some function Z ( t ) such that P e t A P − 1 = ( e t x 0 Z ( t ) e t z ) t ∈ R and hence we deduce that d e t e t A = d e t P e t A P − 1 = e t x e t z = e t ( x + z ) t ∈ R But T r ( A ) = T r ( P A P − 1 ) = x + z so we deduce that d e t e t A = e t T r ( A ) t ∈ R and hence, in particular d e t 2 A = 2 T r ( A ) In this case we deduce that B has determinant 2 5 = 3 2 .